2002
DOI: 10.1007/s00259-001-0661-9
|View full text |Cite
|
Sign up to set email alerts
|

Chronic bacterial osteomyelitis: prospective comparison of 18F-FDG imaging with a dual-head coincidence camera and 111In-labelled autologous leucocyte scintigraphy

Abstract: Indium-111-labelled white blood cells ((111)In-WBCs) are currently considered the tracer of choice in the diagnostic work-up of suspected active chronic osteomyelitis (COM). Previous studies in a limited number of patients, performed with dedicated PET systems, have shown that [(18)F]2'-deoxy-2-fluoro- D-glucose (FDG) imaging may offer at least similar diagnostic accuracy. The aim of this prospective study was to compare FDG imaging with a dual-head coincidence camera (DHCC) and (111)In-WBC imaging in patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
68
0
9

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(77 citation statements)
references
References 15 publications
0
68
0
9
Order By: Relevance
“…18 F-FDG PET has also been evaluated in patients with osteomyelitis. PET has been shown to offer an excellent sensitivity, normally reaching or exceeding 95%, with high specificities above 87% (7,8). In spondylitis and spondylodiscitis, PET combines high sensitivity with high specificity (9-11).…”
Section: Imaging Of Infectious Diseases Osteomyelitismentioning
confidence: 99%
“…18 F-FDG PET has also been evaluated in patients with osteomyelitis. PET has been shown to offer an excellent sensitivity, normally reaching or exceeding 95%, with high specificities above 87% (7,8). In spondylitis and spondylodiscitis, PET combines high sensitivity with high specificity (9-11).…”
Section: Imaging Of Infectious Diseases Osteomyelitismentioning
confidence: 99%
“…• Peripheral bone osteomyelitis (nonpostoperative, nondiabetic foot) (16)(17)(18)(19)(20)(21)(22)(23).…”
Section: Common Clinical Indicationsmentioning
confidence: 99%
“…In one such study, Guhlmann et al [26] highlighted significantly better accuracy of the 18F-FDG PET compared to radiolabeled antigranulocyte antibody in patients with suspected chronic osteomyelitis of the central skeleton including the spine. In a similar study, Meller et al [27] reported that 18F-FDG PET was superior to radiolabeled leukocyte scintigraphy in the axial skeleton. In eight patients, the field of interest was the spine, and 18F-FDG PET showed 100% diagnostic accuracy.…”
Section: The Role Of 18f-fdg Pet/ct In the Diagnosis Of Spinal Infectmentioning
confidence: 93%